Study on end-to-end QoS parameters of TDD-LTE about the services of mobile internet - Zengyi LIU; Shanshan QU; Hong ZHANG (Dianxin kexue)
Aiming at the high bandwidth and service quality demand of wireless access network because of rapid development of mobile internet, the common mobile internet services were analyzed. According to the service characteristic, the 3GPP network protocol specification and the local TDD-LTE network structure which had been deployed, an end-to-end QoS setup model was proposed and QoS parameter deployment verification was performed on a commercial network. The experimental results show that in the resource-consuming scene, the peak user amount of single TDD-LTE cell are increasing by 253.92%; in the real bandwidth-congesting scene, the peak user amount are increasing by 81.80%. The results of the study have good application and popularization.